Cost‐effectiveness of alendronate for the treatment of osteopenic postmenopausal women in Japan. (15th January 2013) - Moriwaki, Kensuke; Komaba, Hirotaka; Noto, Shinichi; Yanagisawa, Shinichiro; Takiguchi, Toru; Inoue, Hiroki; Toujo, Takeshi; Fukagawa, Masafumi; Takahashi, Hideaki E.
Abstract: Many postmenopausal women have osteopenia, a condition characterized by loss of bone mineral density (BMD) that is not as severe as in osteoporosis. The objective of this study was to estimate the cost‐effectiveness of alendronate to prevent fractures in osteopenic postmenopausal women without a history of fracture in Japan. An individual simulation model was developed to predict lifetime costs and quality‐adjusted life years (QALYs) of 5 years of preventive alendronate therapy versus no preventive therapy. The risk of hip and vertebral fracture associated with age and BMD was derived from epidemiologic studies in Japan. We ran the model with different combinations of age (65, 70, and 75 years), BMD (70%, 75%, and 80% of young adult mean [YAM]), and additional clinical risk factors. For 70‐year‐old women with a BMD of 70% of the YAM having one of the following risk factors: a family history of hip fracture, high alcohol intake, or current smoking, the incremental cost‐effectiveness ratio (ICER) of alendronate was 92, 937, 126, 251, and 129, 067 per QALY, respectively. These results were sensitive to age, BMD, and number of clinical risk factors. Probabilistic sensitivity analysis for the base case showed that in the presence of one, two, and three risk factors, alendronate was cost‐effective in 0.2% to 2.6%, 13.1% to 56.1%, and 99.1% of the simulations, respectively, if society is willing to pay 50, 000 per QALY. Additional analysis indicated that alendronate can be a good value in osteopenic women if the 10‐year probability for a osteoporotic hip or vertebral fracture is more than 26.2%. Our results indicate that whether to treat osteopenia with alendronate should be determined on the basis of age, BMD, and number of clinical risk factors in terms of cost‐effectiveness. © 2013 American Society for Bone and Mineral Research